Endothelial Focal Adhesions Are Functional Obstacles for Leukocytes During Basolateral Crawling - Arts, Janine J. G.; Mahlandt, Eike K.; Schimmel, Lilian; Grönloh, Max L. B.; van der Niet, Sanne; Klein, Bart J. A. M.; Fernandez-Borja, Mar; van Geemen, Daphne; Huveneers, Stephan; van Rijssel, Jos; Goedhart, Joachim; van Buul, Jaap D. (Frontiers in Immunology, 2021)
An inflammatory response requires leukocytes to migrate from the circulation across the vascular lining into the tissue to clear the invading pathogen. Whereas a lot of attention is focused on how leukocytes make their way through the endothelial monolayer, it is less clear how leukocytes migrate underneath the endothelium before they enter the tissue. Upon finalization of the diapedesis step, leukocytes reside in the subendothelial space and encounter endothelial focal adhesions. Using TIRF microscopy, we show that neutrophils navigate around these focal adhesions. Neutrophils recognize focal adhesions as physical obstacles and deform to get around them. Increasing the number of focal adhesions by silencing the small GTPase RhoJ slows down basolateral crawling of neutrophils. However, apical crawling and diapedesis itself are not affected by RhoJ depletion. Increasing the number of focal adhesions drastically by expressing the Rac1 GEF Tiam1 make neutrophils to avoid migrating underneath these Tiam1-expressing endothelial cells. Together, our results show that focal adhesions mark the basolateral migration path of neutrophils.